2018
DOI: 10.1016/j.ejmp.2017.09.137
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of coronary bifurcation angle with coronary CT angiography: A phantom study

Abstract: In the phantom setting, both techniques demonstrated a significant correlation to the true bifurcation angle. Despite the lack of agreement of the two techniques in the clinical context, our findings in phantoms suggest that MPR should be preferred to VRT for the measurement of coronary bifurcation angle by CCTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Epidemiological studies have revealed that the distribution of coronary atherosclerosis is inhomogeneous in different branches and in different segments of the same branch [8,9]. Atherosclerosis plaques were more common near the side branches of coronary arteries, and Givehchi [10] et al measured the accurate bifurcation angle to determine the correlation with plaque buildup. The development of atherosclerosis is closely related to endothelial cells and blood flow dynamics [11].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have revealed that the distribution of coronary atherosclerosis is inhomogeneous in different branches and in different segments of the same branch [8,9]. Atherosclerosis plaques were more common near the side branches of coronary arteries, and Givehchi [10] et al measured the accurate bifurcation angle to determine the correlation with plaque buildup. The development of atherosclerosis is closely related to endothelial cells and blood flow dynamics [11].…”
Section: Introductionmentioning
confidence: 99%
“…BAs can be measured using various methods, including coronary computed tomography angiography (CCTA) and QCA. Previous publications reported that measurements by CCTA reflected real BAs in in vitro experiments [ 19 , 20 ]. However, CCTA is not performed before the procedure in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography can be used routinely to assess IMT and plaques 34 . Since atherosclerosis increases the risk of cardiovascular disease, and measurements can be performed noninvasively by carotid artery ultrasonography, this method should be included in screening algorithms for the prevention of cardiovascular events 35 .…”
Section: Discussionmentioning
confidence: 99%